Monetary policy transmission and the labour market in the non-eurozone Visegrad Group Countries in 2000-2014: Evidence from a SVAR Analysis - Przemysław Włodarczyk (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper is aimed at filling the gap in existing economic research by delivering new evidence on the money-labour nexus in the emerging markets of the non-eurozone Visegrad group countries (i.e. Czech Republic, Hungary and Poland). Analyses are based on the Strucutral VAR (SVAR) models of the monetary transmission mechanism, estimated using monthly data from the 2000:1-2014:2 period. In order to obtain impulse responses, the short-run restrictions set, based on the monetary transmission theory, is imposed. Two different identification schemes are considered. The results confirm that there exists a nexus between monetary policy, employment, and unemployment. According to the obtained estimates monetary policy shocks invoked lagged, hump-shaped reactions of output, employment and unemployment in each of the analysed countries.
Keywords: E24; E52; 330; monetary policy; output; employment; unemployment; Visegrad Group countries; Structural Vector Autoregressive models; SVAR